Dismissal of State Civil Apparatus Without Pension Rights by the Head of BKN (Analysis Study of PTUN Decision NO: 85/G/2016/PTUN-BDG) Siyasah Qadhaiyyah Perspective - Lestari, Widya Ayu; Ramadhani Batubara, Putri Eka (LEGAL BRIEF, 2025)
The dismissal of State Civil Apparatus (ASN) without pension rights by the Head of the State Civil Service Agency (BKN) has raised complex legal issues, especially in the context of protecting ASN rights. This study aims to analyze the decision of the State Administrative Court (PTUN) Number: 85/G/2016/PTUN-BDG regarding the dismissal of ASN without pension rights and to assess the decision from the perspective of Siyasah Qadhaiyyah. Siyasah Qadhaiyyah, as one of the branches of science in Islamic fiqh that regulates public policy, provides a different perspective in assessing government policies, including in terms of dismissal of ASN. In this case, the Mayor's Decision Number 881/Kep.117-BKD/VI/2016 concerning the implementation of the Decree of the Head of BKN No. 04755/01/Kep/BHT/TT/2002 is also an important issue, considering that the Mayor's decision is based on the rules issued by the Head of BKN. This analysis shows that there is a discrepancy between the administrative decisions taken by the Head of BKN and the Mayor with the principles of justice in Siyasah Qadhaiyyah, which requires the protection of individual rights, including ASN pension rights. This article aims to provide recommendations regarding a more equitable ASN dismissal policy, by considering broader legal and policy principles